Ambispective study on Mac Donald suturing in pregnant ladies with cervical incompetence in Dhulikhel Hospital - Tamrakur, S R; Chawla, C D (Kathmandu University Medical Journal, 2012)
Background Cervical incompetence is one of the main contributors to repeated pregnancy loss, accounting for approximately 25% of the cases. Typically it results in progressive cervical dilatation, leading to a painless second- or early-third-trimester abortion. Objectives The main objective of the study was to explore the benefit from cervical cerclage in pregnant women with anatomical cervical incompetence Methods In a review of the operation and labour registers from January 2006 till January 2010, a total of 38 cervical cerclage procedures were performed at Dhulikhel Hospital (DH). In the study caste, parity, gestational age, diagnostic criteria, postoperative complications and pregnancy outcomes of the cases were analyzed. Results Two of the 38 cases didn’t come for delivery at Dhulikhel Hospital (Kathmandu University Teaching Hospital). Four women haven’t delivered at the time of data analysis. So pregnancy outcomes were analyzed among 32 cases while rests of the variables were analyzed among 38 cases. Of them 18 cases (47%) were Brahmin, 22 cases (58%) were between 20-25 years old and 32 cases (84%) were from Kavre district.  All cases were booked cases (they had antenatal care in the hospital) and 14 patients (37%) were third gravida. Most cases had 2 to 4 antenatal visits prior to suturing. Two cases were diagnosed with a bicornuate uterus. 21 cases (55%) had a previous history of at least one dilatation and evacuation.  33 cases (87%) were diagnosed with cervical incompetence clinically and confirmed by ultrasound. The remaining 13% were assessed, in the absence of a history of mid-trimester abortion, of having a high suspicion of cervical incompetence after mid-trimester scan with measurement of cervical length. In 18 cases (47%), cervical cerclage were done at 15 to 20 weeks of gestation. The postoperative period was uneventful in all 38 cases.  All cases (32) delivered in DH were assisted by consultant obstetricians. 19 out 32 cases (59%) were delivered vaginally at term. Conclusions38 cases were included in the study. Pregnancy outcomes were analyzed among 32 cases while rests of the variables were analyzed among 38 cases. 31 out 32 cases were delivered with good foetal weight. It clearly shows pregnant women with anatomical cervical incompetence were benefitted from cervical cerclage. The authors recommend an early trans vaginal scan in any patient with a history of mid trimester abortion or preterm labour. The cervical cerclage procedure therefore should be available more widely to benefit those patients with proven or strongly suspected cervical incompetence.DOI: http://dx.doi.org/10.3126/kumj.v8i3.6222 Kathmandu Univ Med J 2010;8(3):321-24